Socio-Environmentally Responsible Hotel Business: Do Tourists to Penang Island, Malaysia Care? - Kasim, Azilah (Taylor & Francis Group, 2004)
Over the last decade, there has been a growing awareness within the global hotel industry of the relevance for environmental protection issues. Hotel corporations are seen to be changing their image by engaging in environmental initiatives. Some hotels even go further to include social responsibility issues in their agenda. Greater awareness on the potential economic and other less direct benefits of environmentally-friendly measures, coupled with the establishment of many “watch dog” and support organizations such as the International Hotel and Restaurant Association (IHRA) and Green Hotel Association (GHA) has fueled the rise of “green” and/or responsible hotels in many established tourism destinations. Nevertheless, environmental and social measures are not the traditional core competency of a hotel. Thus, “green” and responsible measures may require additional investment and organizational change. From a business perspective, additional investments are futile if they do not result in higher market share. Simply put, a hotel's “green” and responsible measures are meaningless if met only with consumer apathy. Therefore, to justify the need for hotels to engage in responsibility measures, one of the questions that must be answered is-do the tourists care about hotels' social and environmental responsibility? Unfortunately, there is still little empirical knowledge of tourists' demand for responsible hotels, particularly within the context of a developing country such as Malaysia. This paper attempts to narrow the gap of information by providing a preliminary outlook on the “demand” of tourists for green and socially responsible hotels in Penang Island, Malaysia. Specifically, it looked at the main criteria tourists use when choosing a hotel, their preferences as well as their attitude, interest and opinion relating to a hotel's green and socially responsible measures.